Non-HDL-C/HDL-C ratio is associated with carotid plaque stability in general population: A cross-sectional study - Wang, Anran; Li, Yapeng; Zhou, Lue; Liu, Kai; Li, Shaohua; Zong, Ce; Song, Bo; Gao, Yuan; Li, Yusheng; Tian, Chuansheng; Xing, Yurong; Xu, Yuming; et al. (Frontiers in Neurology, 2022)
Abstract Background: Carotid plaque plays an important role in the development of stroke，especially unstable plaque. A novel lipid ratio, the non-HDL-C/HDL-C ratio, contains both atherogenic and anti-atherogenic particles information, and has been shown to be associated with carotid atherosclerosis. However, few population-based studies have evaluated the association between non-HDL-C /HDL-C ratio and carotid plaque stability. Methods: This study was carried out on 27,436 urban workers aged 20 years or older who participated in a comprehensive health screening between January 2016 and December 2017 at the First Affiliated Hospital of Zhengzhou University, China. Carotid plaque was assessed using ultrasonography. Multinomial logistic regression models were used to explore the relationship between the non-HDL-C/HDL-C ratio and carotid plaque stability by odds ratios (ORs) and 95% confidence intervals (CIs). Subgroup and sensitivity analysis were performed to verify the robustness of the results. Results: Carotid plaque was detected in 7,161 (26.1%) respondents, with stable and unstable plaque accounting for 3,277 (11.9%) and 3,884 (14.2%), respectively. There was a significant positive association between the prevalence of carotid plaque and non-HDL-C/HDL-C ratio quartile levels, and the same associations were observed for the prevalence of stable and unstable carotid plaque (P for trend < 0.001). The mean non-HDL-C /HDL-C ratios of non-carotid plaque (mean ± SD, 2.9 ± 1.1), stable carotid plaque (mean ± SD, 3.2 ± 1.2) and unstable carotid plaque (mean ± SD, 3.4 ± 1.4) increased gradually (P＜0.001). In multinomial logistic regression, ORs (95% CIs) for the highest versus lowest quartile of the non-HDL-C /HDL-C ratio were 1.70 (1.48–1.95) between stable carotid plaques and no carotid plaque, 2.34 (2.06–2.67) between unstable carotid plaques and no carotid plaque, and 1.38 (1.18–1.61) between unstable carotid plaques and stable carotid plaque, after adjusting for common cardiovascular risk factors. Conclusion: Our findings suggested that the non-HDL-C/HDL-C ratio was significantly associated with carotid plaque stability and might be a useful indicator for the early identification of high-risk carotid plaque.